Outburst Flood Simulation Model for Optimizing the Solo River Floods Emergency Response Activities - Priyana, Yuli; Priyono, Priyono; Anna, Alif Noor; Sigit, Agus Anggoro (Forum Geografi, 2014)
This study aims to develop flood inundation based on several flood level. The results of this study are: (a) land use in the study area is divided into (1) urban area (the Business Area) which includes regional administrative center, shopping area, and office area, (2) residential areas (single home region, the region multi- unit house (residence), settlement areas and apartments), (3) industrial estate (industrial estates are less dense and dense industrial area), (4) the surface area covered with vegetation (forest - thicket, meadow area, and the area of land productive rice fields and fields), (5) the area of open land and vacant land that is intended (the city park , cemetery and park area, and (6) transportation area and the pavement surface area (area train station and bus terminal region), (b) the preparation of spatial database in this study in the form of data or data vector altitude of Digital Elevation Model (DEM). District of Jebres there are 56 points of elevation and District of Pasar Kliwon there are 48 points of elevation. Elevation of the study area ranged from 88,9 mpdal up to 127.65 mdpal and (c) the higher the flood inundation scenarios impact on land use in the study area are also getting bigger. Most obvious impact under scenario 2 m area of 296 601 m , while the smallest impact under scenario 1 m with an area of 77 693 m 2 2 impact. Extensive simulation results based on the total impact amounts to 544 756 m.